Cooperative Integrated Reading and Composition (CIRC) Method in Arabic Language Learning - Amin Nasir; Choirun Niswah; Muhammad Adam Muhammad Abdel Ali (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2025)
This study investigated the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) method in improving students’ Arabic reading comprehension. The research focused specifically on three reading competencies: identifying main ideas, understanding contextual vocabulary, and interpreting the overall meaning of Arabic texts. The study employed a quantitative approach using a quasi-experimental design with a control and experimental group. Data were collected through pretest and posttests consisting of 25 multiple-choice questions, which were validated and tested for reliability (Cronbach’s Alpha = 0.897). Additional documentation and classroom observation were used to ensure the procedural integrity of the method’s implementation. Results showed that students taught using the CIRC method achieved a significantly higher gain in reading scores, with an N-Gain of 41.7% (moderately effective), compared to 16% in the control group (ineffective). The simple linear regression test confirmed a statistically significant effect (sig = 0.000) with 41% of the reading improvement attributed to the CIRC method. These findings suggest that CIRC enhances students' reading skills by encouraging active participation, group discussion, and collaborative summarization. Although not all students benefited equally, the structured and interactive nature of CIRC helped overcome reading difficulties often associated with learning Arabic as a foreign language